Psychospiritual guidance frameworks in dealing teenagers with delinquent - Saparudin, Intan Farhana; Che Soh, Siti Nabilah; Nordin, Shah Rul Anuar; Ahmad, Shakila; Siti Marpuah, Siti Marpuah (Hampstead Psychological Associates, 2020)
The phenomenon of current social phenomena that occur every day shows a wide range of social problems of society that are not only from the civic consciousness, family functioning and environmental issues, but the most important is the problem of morale, morality and personality among the youth. Symptoms such as bullying, smoking, damaging public property and stealing which are common and unstoppable eventually lead to heavier crimes such as robbing, killing, sex and drug addiction. The act is known as delinquent among the underage adolescents while for the youth is devian or criminal behavior. This situation undermines public order and social harmony that is responsible for every member of the community to save the youth from continuing to a more dangerous scene. Thus a preliminary study of interventions and guidance from the islamic psychospiritual is identified as a step towards addressing delinquents. The objective of the article is to identify the dimensions of Islamic psychospiritual according to the views of Islamic and Western psychologists. In achieving the objectives the content analysis method (content analysis) is done. The findings show that is an integrated psychospiritual framework involves psychological and spiritual guidance in dealing with delinquent youth. The implication of this study is expected to provide early information on integrated guidance from psychospiritual dimension towards teenagers with delinquent symptoms.